Diagnostic Accuracy of Magnetic Resonance Enterography for the Evaluation of Active and Fibrotic Inflammation in Crohn’s Disease - Loch, Florian N.; Kamphues, Carsten; Beyer, Katharina; Klauschen, Frederick; Schineis, Christian; Weixler, Benjamin; Lauscher, Johannes C.; Dorenbeck, Marc; Bayerl, Christian; Reiter, Rolf (Frontiers in Surgery, 2022)
Background: Despite the success of standard magnetic resonance enterography (MRE) in detecting Crohn’s disease (CD), characterization of strictures and thus therapy guidance is still limited. The aim of the study was to determine diagnostic accuracy of MRE in detecting or ruling out active inflammation and identifying fibrotic lesions in patients with terminal ileal CD with histopathology as reference. Methods: Sixty-seven consecutive patients (median age 32 years, range 19-79 years) with terminal ileal CD were retrospectively enrolled between January 2015 and October 2020. The median interval between MRE and surgery was 9 days (range 0-86 days). Sensitivity, specificity, positive and negative predictive value (PPV and NPV, respectively), and area under the curve (AUC) with 95%-confidence intervals (CI) were calculated for the MRE-based AIS (acute inflammation score) using histopathology of surgical specimens as reference standard. Results: Sensitivity, specificity, PPV and NPV for detecting or ruling out active inflammation were 100% (CI: 0.94-1.00; 0.44-1.00; 0.93-1.00; 0.31-1.00) using an AIS cut-off of >4.1. AUC was 1.00 (CI: 1.00-1.00; p<0.01). In all patients with fibrotic changes only and no active inflammation, AIS was <4.1. Interobserver agreement was substantial (κ=0.65, p<0.01). Conclusions: Our study has shown an excellent diagnostic performance of the MRE-based AIS for determining whether active inflammation is present or lesions are due to chronic changes in ileal CD using histopathology of surgical specimens as reference. These findings indicate that the MRE-based AIS allows better determination of the inflammatory stage of terminal ileal CD, which facilitates the decision to perform surgery.